If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = -8v + 2(v + -8) Reorder the terms: -10 = -8v + 2(-8 + v) -10 = -8v + (-8 * 2 + v * 2) -10 = -8v + (-16 + 2v) Reorder the terms: -10 = -16 + -8v + 2v Combine like terms: -8v + 2v = -6v -10 = -16 + -6v Solving -10 = -16 + -6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '6v' to each side of the equation. -10 + 6v = -16 + -6v + 6v Combine like terms: -6v + 6v = 0 -10 + 6v = -16 + 0 -10 + 6v = -16 Add '10' to each side of the equation. -10 + 10 + 6v = -16 + 10 Combine like terms: -10 + 10 = 0 0 + 6v = -16 + 10 6v = -16 + 10 Combine like terms: -16 + 10 = -6 6v = -6 Divide each side by '6'. v = -1 Simplifying v = -1
| 18+16-5+4= | | -1=-8+x/-2 | | -16y(y-18)= | | 6(x-11)=x+9 | | 2.5k+5-1.5k=14 | | a/-3+3=8 | | z=5-28z | | 7(3m-5)-5(1+m)=0 | | 0=-16t^2+20t+24 | | x^3+x^2-12x-10=0 | | x/23=0.5 | | 55-6(3b-1)=-11 | | x/23=50 | | 9X1/2=38 | | 16y-8xy+yx^2=0 | | 4y-8y=5 | | 13=4x-9 | | 4+x=5x | | -131=-8(m+7)-7m | | 3(d-8)-5=9(9d+2)+1 | | -105=6(3r-4)-9r | | -49-9v=2-7(v+5) | | 4+3a-8-2a= | | y/4=-5-6 | | 7y+6+4y-13=26 | | 17=4x-4-(-3x) | | -22-10x=-2(6x+1) | | 3(4x+3)=12x+9 | | f(x)=4x^2-1 | | -50-5n=10(6+5n) | | -32x+63x^2-63=0 | | abs(2x+2)=20 |